Practical oracle database appliance - Curtis, Bobby (Apress, 2014)
Practical Oracle Database Appliance is a hands-on book taking you through the components and implementation of the Oracle Database Appliance. Learn about architecture, installation, configuration, and reconfiguration. Install and configure the Oracle Database Appliance with confidence. Make the right choices between the various configurations in order to realize your performance requirements. Manage and monitor the appliance to meet business requirements. Protect your data through proper backup and recovery procedures. Oracle Database is one of the most relied-up databases in industry. For many years Oracle Database was a software product that had to be installed and configured at no small expense. The Oracle Database Appliance makes Oracle Database into a plug-and-play proposition: Plug the appliance into the wall socket, and turn it on. That's it. You have a running database server. This book takes you through that beginning point and beyond, helping you to realize in your own organization the ease of deployment and management represented by the appliance. Covers the Oracle Database Appliance from architecture through configuration. Provides a technical resource for system- and database administrators. Examines practical use cases for the Oracle Database Appliance.